Gender and communication issues in the Malaysian public universities - Tamby Chek, Ibrahim; Syed Mohamad, Syed Ismail; Jusoff, Kamaruzaman; Abd Razak, Ahmad Zainal Abidin; Mat Norwani, Norlia; Abdullah, Muhammad Khairuddin Lim (IDOSI Publications, 2011)
Gender and communication is a hot topic discussed and research on this topic is a never-ending effort. This study will discuss issues of gender and communication in the Malaysian public universities. Among the major items focused in this study is the advancement of women in the workforce, the major barriers that prevent women from climbing up the corporate ladder, and the management of conflict and anger in order to build a conducive and therapeutic work setting. The appointment of two women vice chancellors in the Malaysian public universities shows that the glass ceiling can be broken and women can excel further in the Malaysian workforce. This phenomenon indicates that women are also important in the policy-making and decision-making process in public universities.